Study of Surface Modification of Ultra-Fine CaCO3 With Different Coupling Agent - Cheng, Guojun; Yu, Xiuhua; Ding, Guoxin; Xu, Chuyang (Asian Journal of Chemistry, 2013)
To compare the superficial capacity of ultra-fine calcium carbonate powder, the coupling agents of g-aminopropyl triethoxyl silane (KH550), g-methacryloxypropyl trimethoxy silane (KH-570), vinyltrimethoxy silane (SG-Si 171) and di(dioctylpyrophosphato)ethylene titanate (NDZ-311) were used as modifiers to modify its surface activity. The structural changes and properties of the unmodified and modified ultra-fine CaCO3 powder were characterized by Fourier transform infrared spectroscopy, contact angle measuring instrument (CAMI) and sedimentation stability experiment. The results showed that the coupling agent bonds covalently onto the surface of CaCO3 particles and forms an organic coating layer. Contact angle measuring instrument indicated that the coupling agent molecules were absorbed or anchored on the surface of CaCO3 particles, which facilitates to hinder the aggregation of CaCO3 particles.